Wildflowers : A TOON Book - Liniers 1973- (New York : TOON Books, 2021)
Sisters Clemmie, Matilda, and Emma embark on an adventure of the imagination through the jungles of a mysterious island after a plane crash, which reveals the unbreakable bond they share.
Keywords: Sisters -- Comic books, strips, etc; Adventure and adventurers -- Comic books, strips, etc; Imagination in children -- Comic books, strips, etc; Sisters -- Fiction; Adventure and adventurers -- Fiction; Imagination -- Fiction; Cartoons and comics; Comics (Graphic works)